Effects of Macroeconomic News on Hong Kong Bond Market: An Intraday Empirical Evidence. - Chowdhery, Sarah Hafeez (2010)
This research paper investigates the effect of six macroeconomic news announcements on the Hong Kong bond market. The five bonds chosen for the purpose of this study are; two year sovereign debt bond, five year government Treasury bond, seven year corporate market bond, ten year government Treasury bond and thirteen year corporate market bond. In particular we look at the effect of the six macroeconomic news announcements on bond prices and bond bid-ask spreads. The effect of the magnitude or the size of the surprise element on the bond is also investigated. We find three out of the six macroeconomict announcements to affect the government and corporate bonds significantly. We also find a widening of spreads after announcements for government Treasury bonds and a narrowing of spread for corporate market bonds. In conclusion, we find the government Treasury bonds to be more responsive than corporate market bonds.